KAMPANYE PLAN INTERNATIONAL DALAM PARTISIPASI KEPEMIMPINAN ANAK PEREMPUAN DI INDONESIA - Annisa, Nur; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Plan International is a community and humanitarian development organization focused on children and equality for girls. Commit to making a long-term plan for the lives of vulnerable and marginalized children to promote equality. Plan International created a global movement called Girls Get Equal. In this movement, there are Girls Leadership activities that can increase leadership in girls. The purpose of this writing is to explore the efforts made by Plan International and Plan International Indonesia in campaigning the global GGE movement for the leadership of girls in Indonesia.Girls Get Equal focuses on giving girls strength and opportunity. Girls Get Equal campaign we can better face gender norms of all girls problems and achieve girls right. GGE is a campaign framework that provides an overall idea and is supported by good reason. The main focus of the Plan is to prioritize girls problems such as; education, health, child marriage, teenage pregnancy. Plan invites agencies that have the power to stand together in fulfilling the right of children and girls.The conclusion of this study has led to a number of result. First; Plan International carries out activitiesInternational Day of the Girls in the Girls Get Equal campaign. Second; With the activities of the IDG commemoration, Plan created an activity called Girls Leadership, and we will see that girls are able to become leaders and can get the same opportunities in leading. Third; the mechanism of Girls Leadership activities, also called Girls Takeover, which later selected girls will lead in several agencies, both Government and non-government.Keywords: Gender Equality, Girls, Girls Get Equal, Plan International